When achievement striving goes awry: Challenging the dual nature of perfectionism - Hall, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
This presentation sets out to challenge arguments put forward in support of the dual nature of perfectionism. In particular, the idea that perfectionism, with its accompanying tendency for overly critical evaluation (Stoeber, 2011), can manifest as a universally constructive quality, which not only activates striving to achieve exacting standards, but elicits performance appraisal processes with the capacity to sustain adaptive patterns of motivation and foster psychological well-being. The presentation will demonstrate that perfectionism is a complex multidimensional personality characteristic that reflects an irrational way of thinking about achievement, which makes it difficult to sustain adaptive motivational qualities and endorse personal mastery especially when experiencing adversity (Flett & Hewitt, 2016; Hall 2016). While perfectionism may energise motivation and bring about exceptional accomplishments, under adverse conditions it is always likely to trigger dysfunctional cognition that may lead to performance impairment and emotional distress. The presentation will outline why perfectionism is best thought of as a source of vulnerability in sport participants and it will offer some thoughts about research strategies that might be employed to examine that contention. It will first reflect upon the paradoxical effects of perfectionism and challenge arguments put forward to suggest that perfectionism can manifest in both adaptive and maladaptive forms. It will further contend that whether perfectionism is considered to be a trait, an inter-personal style or a pattern of ruminative thought, it is difficult to argue that it is capable of evoking universally adaptive qualities that will facilitate either sustained performance or psychological well-being in athletes performing at any level, unless it is accompanied by other sources of resilience. The presentation will then outline important psychological mechanisms and processes that are elicited by perfectionistic thinking, in order to illustrate why perfectionism is a vulnerability factor. It will critically evaluate the emerging research base in sport and physical activity to explain what is known about the influence of perfectionism. Finally, it will provide some thoughts on new research directions which will further challenge arguments that have been put forward in support of the dual nature of perfectionism.